The Design and Implementation of the Eth2Bee for the Ethernet to ZigBee Gateway - Shim, Jaechang; Ko, Jooyoung (Recent Advances in Communications and Networking Technology, 2014)
We present the design, prototyping, implementation, and test of Eth2Bee for the Xbee to Ethernet gateway for wireless personal area network. It supports ZigBee, WIFI, and Bluetooth. The Eth2Bee board is very useful for configuring in low power wireless sensor networks. Eth2Bee system is a combination of two technologies: Ethernet technology based on wired LAN technology and ZigBee technology based IEEE 802.15.4 standard WLPAN(Wireless Low-power Personal Area Network). This paper proposes the design, implementation, and test of Eth2Bee board hardware. We install the firmware into Eth2Bee and then install the Web service software for applications. Sensed data is passed to the Web through ZigBee wireless communications. We tested the prototyped Eth2Bee system and it gave good performance.
Keywords: sensor network